Encyclopedia of networking : electronic edition - Sheldon, Tom. (Berkeley : Osborne McGraw Hill, 1998)
Encyclopedia of networking; Networking terms and concepts; All major networking systems covered; Reference.
Keywords: Encyclopedia; Computers; Electronics; Computer networking; Computer networks -- Encyclopedias